Searching for evidence of PeVatron activity from stellar clusters via gamma-ray and neutrino signatures - Mitchell, Alison; Celli, S.; Specovius, Andreas; Morlino, G.; Menchiari, S. (Proceedings of Science, 2024)
Young and massive stellar clusters are a promising source class for the acceleration of galactic cosmic rays to PeV energies. Supernova explosions of massive stars lead to semi-continuous injection of cosmic rays into the cluster environment. Collective stellar winds form a wind-blown bubble with a termination shock at which further particle acceleration may occur. Interactions of such energetic hadronic particles with target material - such as molecular clouds - will generate signature gamma-ray and neutrino emission. We apply a model of cosmic ray acceleration in stellar clusters to catalogues of known stellar clusters, identifying the most promising targets to search for evidence of PeVatron activity. Predictions for the secondary fluxes of gamma-ray and neutrino emission are derived based on particle acceleration at the collective wind termination shock. Our results are compared to data available from the H.E.S.S. Galactic Plane Survey, and we estimate the detection prospects for current and future generation neutrino experiments.
CRIS-Team Scopus Importer:2025-02-04